1992
DOI: 10.1038/nbt0992-1030
|View full text |Cite
|
Sign up to set email alerts
|

Oligonucleotide and Amplification Fingerprinting of Wild Species and Cultivars of Banana (Musa spp.)

Abstract: DNA oligonucleotide and amplification fingerprinting have been successfully used to detect genetic polymorphisms in 15 representative species and cultivars of the genus Musa, comprising AA, AAA, AAAA, AAB, ABB, and BB genotypes. In-gel-hybridization of Hinf I-digested genomic banana DNA to the 32P-labeled synthetic oligonucleotides (GATA)4, (GTG)5, and (CA)8 revealed considerable polymorphisms between Musa species and cultivars. The fingerprint patterns proved to be somatically stable and did not show differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
9

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(68 citation statements)
references
References 14 publications
1
58
0
9
Order By: Relevance
“…RAPD analysis has been used for constructing trees in other organisms (Chalmers et al, 1992;Kaemmer et al, 1992;Megnegneau et al, 1993;Tibayrenc et al, 1993). We have observed that small alterations in PCR parameters or quality of target DNA can radically alter RAPD patterns (see also, Devos & Gale, 1992; Williams et a!., 1993).…”
Section: Discussionmentioning
confidence: 99%
“…RAPD analysis has been used for constructing trees in other organisms (Chalmers et al, 1992;Kaemmer et al, 1992;Megnegneau et al, 1993;Tibayrenc et al, 1993). We have observed that small alterations in PCR parameters or quality of target DNA can radically alter RAPD patterns (see also, Devos & Gale, 1992; Williams et a!., 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies (e.g., Kaemmer et al 1992) have reported on a more limited sample of clones than those held by major genebanks. During the next few years molecular technologies will be more widely employed for measuring the breadth and gaps in large collections of vegetatively propagated plants.…”
Section: Plant Genetic Resource Management a Genetic Markers Anmentioning
confidence: 99%
“…Random-amplified polymorphic DNA (RAPD) markers (Williams et al, 1990) have been successfully used for cultivar analysis in a number of plant species. These include the following: broccoli and cauliflower (Hu and Quiros 1991;Kresovich et al, 1992), cocoa (Wilde et al, 1992), banana (Kaemmer et al, 1992;Howell et al, 1994), papaya (Stiles et al, 1993), apple (Koller *To whom correspondence should be addressed. Tel: 88-2-966-1920-59 (6102);Fax: 88-2-861-5583 E-mail: haseena@bangla.net et al, 1993), celery (Yang and Quiros et al, 1993), onion (Wilkie et al, 1993), cranberry (Novy et al, 1994), sunflower (Lawson et al, 1994), rice (Takeuchi 1994), maize (Yazaki et al, 1994), Brassica juncea (Fujushiro et al, 1994), soybean (Lin, 1996;Powel, 1996), rose (Denbener et al, 1996), kenaf (Zhou et al, 1998;Cheng et al, 2000), roselle (Hanboonsong et al, 2000), and jute (Belayat et al, 2002).…”
Section: Introductionmentioning
confidence: 99%